2011
DOI: 10.2478/s11535-011-0059-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of red and blue light-emitting diode illumination on radish physiological indices

Abstract: The objective was to evaluate the effect of different combinations of red (638 nm) and blue (455 nm) light produced by solid-state light-emitting diodes (LEDs) on physiological indices (net assimilation rate, hypocotyl-to-leaf ratio, leaf area, leaf dry weight, hypocotyl length and diameter, plant length, developed leaves), variation of photosynthetic pigments and non-structural carbohydrates in radish (Raphanus sativus L., var. ‘Faraon’). Lighting experiments were performed under controlled conditions (total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
8
19
0
Order By: Relevance
“…The lower leaf LA and plant height in treatments with high B/R light ratios may be associated with a B light-mediated inhibition of cell expansion [46]. A similar result was reported by Samuoliene et al [47], who showed that an optimal combination of B/R light ratios enhances the plant growth rate in controlled conditions. However, the optimal B/R ratio differed according to plant species, growth periods, and the targeted qualities [48].…”
Section: Lettuce Morphology Characteristics Are Affected By the B/r Lsupporting
confidence: 80%
“…The lower leaf LA and plant height in treatments with high B/R light ratios may be associated with a B light-mediated inhibition of cell expansion [46]. A similar result was reported by Samuoliene et al [47], who showed that an optimal combination of B/R light ratios enhances the plant growth rate in controlled conditions. However, the optimal B/R ratio differed according to plant species, growth periods, and the targeted qualities [48].…”
Section: Lettuce Morphology Characteristics Are Affected By the B/r Lsupporting
confidence: 80%
“…Speci cally, compared to white light, the red light signi cantly increased the plant height and decreased the stem diameter and leaf area, whereas blue light signi cantly suppressed the height and leaf area of S. glabra. Similar ndings were also obtained in previous studies, for instance, radish stems were found to be thin and elongated under red light [38]. In experiments on the effects of blue and red light on stem elongation of tomato seedlings and other species, results showed that stem length decreased with increasing blue to red light ratio [39,40].…”
Section: Effects Of Different Led Lights On Plant Morphological Traitssupporting
confidence: 89%
“…Speci cally, red light enhanced plant growth while blue light restricted it. Similar ndings were also obtained in previous studies; for instance, radish stems were found to be thin and elongated under red light [38]. In experiments on the effects of blue and red light on stem elongation of tomato seedlings and other species, results showed that stem length decreased with increasing blue to red light ratio [39,40].…”
Section: Effects Of Different Led Lights On Plant Morphological Traitssupporting
confidence: 89%